EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN PADA DIKLAT FUNGSIONAL GURU MUDA MADRASAH IBTIDAIYAH ANGKATAN IV DI BALAI DIKLAT KEAGAMAAN BANDUNG TAHUN 2018 - Niar Yuniarti (Balai Diklat Keagamaan Bandung, 2018)
This study aims to determine the effectiveness of instructional media in the teaching and learning process in educational classes in the Functional Training of Junior High School Madrasah Ibtidaiyah class IV in the Ministry of Religion of West Java Province. district / city in West Java Province. The results showed that using appropriate and effective media would improve understanding in receiving the material provided during the training. So the use of power points in the implementation of learning is better understood and well received. The use of materials / slides in learning in the training facilitates the transfer of knowledge and the use of handouts to maximize the learning process so that participants will be more focused on one given material and the use of focus and laptop must be mastered by widyaiswara because it makes it easier to do the learning process so that bridging activities that are felt more time consuming then in broad outline this learning media is more effective and efficient in learning in education. Key words: Effectiveness, learning, instructional media.